Avoiding Treatment Failures in the Anxiety Disorders - Otto, Michael; Hofmann, Stefan; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Extensive studies have shown cognitive-behavioral therapy to be highly effective in treating anxiety disorders, improving patients$1 (Bsocial functioning, job performance, and quality of life. Yet every CBT clinician faces some amount of client resistance, whether in the form of "This won$1 (Bt work," "I$1 (Bm too depressed," or even "You can$1 (Bt make me!" Avoiding Treatment Failures in the Anxiety Disorders analyzes the challenges presented by non-compliance, and provides disorder- and population-specific guidance in addressing the impasses and removing the obstacles that derail therapy. Making use of extensive clinical expertise and current empirical findings, expert contributors offer cutting-edge understanding of the causes of treatment complications$1 (Band innovative strategies for their resolution$1 (Bin key areas, including: The therapeutic alliance The full range of anxiety disorders (i.e., panic, PTSD, GAD) Comorbidity issues (i.e., depression, personality disorders, eating disorders, substance abuse, and chronic medical illness) Combined CBT/pharmacological treatment Ethnic, cultural, and religious factors Issues specific to children and adolescents Both comprehensive, and accessible, Avoiding Treatment Failures in the Anxiety Disorders will be welcomed by new and seasoned clinicians alike. The window it opens onto this class of disorders, plus the insights into how and why this treatment works, will also be of interest to those involved in clinical research.s
General Aspects of Treatment Complications -- A Case Formulation Approach to Resolve Treatment Complications -- Helping Exposure Succeed: Learning Theory Perspectives on Treatment Resistance and Relapse -- Therapeutic Alliance and Common Factors in Treatment -- Combined Cognitive Behavioral and Pharmacologic Treatment Strategies: Current Status and Future Directions -- Cultural Considerations and Treatment Complications -- Avoiding Treatment Failures: Disorder-Specific Perspectives -- Avoiding Treatment Failures in Panic Disorder -- Avoiding Treatment Failures in Obsessive Compulsive Disorder -- Avoiding Treatment Failures in PTSD -- Avoiding Treatment Failures in Social Anxiety Disorder -- Avoiding Treatment Failures in Generalized Anxiety Disorder -- Avoiding Treatment Failures in Specific Phobias -- Treatment Complications in Special Populations -- Resolving Treatment Complications Associated with Comorbid Depression -- Resolving Treatment Complications Associated with the Presence of Comorbid Personality Disorders -- Resolving Treatment Complications Associated with Comorbid Anxiety and Substance Use Disorders -- Resolving Treatment Complications Associated with Comorbid Eating Disorders -- Resolving Treatment Complications Associated with Comorbid Medical Conditions -- Resolving Treatment Complications in Children and Adolescents.
Keywords: Philosophy (General).; Psychotherapy; Psychology, clinical; Psychology; Clinical Psychology; Psychotherapy